1999
DOI: 10.1099/13500872-145-6-1349
|View full text |Cite
|
Sign up to set email alerts
|

Mucoid conversion of Pseudomonas aeruginos by hydrogen peroxide: a mechanism for virulence activation in the cystic fibrosis lung

Abstract: The leading cause of mortality in patients with cystic fibrosis (CF) is respiratory failure due in large part to chronic lung infection with Pseudomonas aeruginosa strains that undergo mucoid conversion, display a biofilm mode of growth in vivo and resist the infiltration of polymorphonuclear leukocytes (PMNs), which release free oxygen radicals such as H202. The mucoid phenotype among the strains infecting CF patients indicates overproduction of a linear polysaccharide called alginate. T o mimic the inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
400
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 449 publications
(419 citation statements)
references
References 50 publications
13
400
1
3
Order By: Relevance
“…2) is in agreement with in vitro studies showing that this homopolymeric tract is prone to single nucleotide deletion upon exposure of P. aeruginosa biofilms to reactive oxygen species, a scenario envisaged to occur in the CF lung (Mathee et al, 1999).…”
Section: Locussupporting
confidence: 76%
See 1 more Smart Citation
“…2) is in agreement with in vitro studies showing that this homopolymeric tract is prone to single nucleotide deletion upon exposure of P. aeruginosa biofilms to reactive oxygen species, a scenario envisaged to occur in the CF lung (Mathee et al, 1999).…”
Section: Locussupporting
confidence: 76%
“…1). Since it is extremely unlikely that three *The alginate contents of the PAO1 strain and of its isogenic PDO300 mutant (Mathee et al, 1999) harbouring the mucA stop mutation DG430 were 0?01 and 2?7 mg uronic acid (mg protein) 21 , respectively.…”
Section: Locusmentioning
confidence: 99%
“…The prototypic non-mucoid P. aeruginosa strain PAO1 (Holloway & Morgan, 1986) and its isogenic derivatives were used. These derivatives were the mucoid strain Alg þ PAOmucA22 (PDO300), which carries the mucA22 allele that results in constitutive production of alginate (Mathee et al, 1999), and PAOalgD, a nonmucoid strain that carries a deletion in algD (Garrett et al, 1999). Strains were cultured in LB broth (l À1 : 10 g tryptone, 5 g yeast extract and 5 g NaCl) overnight at 37 8C and bacterial cells were harvested by centrifugation and resuspended in saline to approximately 1·5 3 10 8 c.f.u.…”
Section: Methodsmentioning
confidence: 99%
“…starvation, antibiotic treatment, slow growth rate, ethanol dehydration, high osmotic pressure or high ionic strength (Evans & Linker, 1973;Govan & Fyfe, 1978;DeVault et al, 1990;Terry et al, 1991). We have demonstrated that local accumulation of activated polymorphonuclear cells (PMNs) exerts selective pressures on the bacteria from phagocytosis and oxygen free radicals, resulting in conversion from the non-mucoid to the mucoid phenotype (Mathee et al, 1999). Approximately 84 % of mucoid CF isolates have mutations in the mucA gene, which encodes a negative regulator of an alternative sigma factor, AlgT/U (Boucher et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in mucA are often responsible for the switch to the mucoid phenotype in clinical isolates (5). Antibiotics as well as components of host defensive processes may contribute to mucA mutations and to the accompanying phenotypic switch from non-alginate-producing strains and acute infections to alginate-producing strains and chronic infections (42,53).…”
mentioning
confidence: 99%